2012
DOI: 10.1100/2012/652150
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Metals in Surface Water and Sediment in the Langat River and Geochemical Factors That Influence Their Water-Sediment Interactions

Abstract: This paper determines the controlling factors that influence the metals' behavior water-sediment interaction facies and distribution of elemental content (75As, 111Cd, 59Co, 52Cr, 60Ni, and 208Pb) in water and sediment samples in order to assess the metal pollution status in the Langat River. A total of 90 water and sediment samples were collected simultaneously in triplicate at 30 sampling stations. Selected metals were analyzed using ICP-MS, and the metals' concentration varied among stations. Metal concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…Based on the result, the value of these variables are very low and below guidelines (except Zn). This VF is consider as surface runoff and the natural geologic sources [2,40]. Based on [40], topsoil and rocks are drained by rainwater during north-east monsoon season and settled on sediment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the result, the value of these variables are very low and below guidelines (except Zn). This VF is consider as surface runoff and the natural geologic sources [2,40]. Based on [40], topsoil and rocks are drained by rainwater during north-east monsoon season and settled on sediment.…”
Section: Resultsmentioning
confidence: 99%
“…This VF is consider as surface runoff and the natural geologic sources [2,40]. Based on [40], topsoil and rocks are drained by rainwater during north-east monsoon season and settled on sediment. Yet, Zn gives strong negatives loading because of this element are higher at Semerak Lagoon which come from river discharge from upstream environment [41][42].…”
Section: Resultsmentioning
confidence: 99%
“…Samples collection points in the estuary into the river and along the coastal area are shown in Figure 1 and Table 1. Hill, mountainous terrain and coastal plain are surrounding the basin [11]. The water flows from the upstream area in Hulu Langat to Kuala Langat at the downstream area where the Langat River becomes the main river in the basin which flows in a south western direction and drains into the Straits of Malacca.…”
Section: Methodology Study Area and Sampling Sitementioning
confidence: 99%
“…In this study, Langat river estuary is chosen for study area due to the basin underlain by schist, phyllite and granite rock formation [11]. The estuary also acts as a resource for fisheries and aquaculture projects that gives important role in ecology, tourism and as natural resources such as mangrove forest [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other results showed that the element removal process of dissolved Pb and Zn in Gota estuary, Sweden, ineffectively occurred, as the estuary type were salt wedge and unpolluted. Lim et al (2012) who studied the Langat River, Malaysia, found that Pb concentration in the sediment was tended to be higher than in the water column. The phenomena showed that Pb has a larger adsorption capacity.…”
Section: Behavior Of Pb and Zn In The Watersmentioning
confidence: 99%